Y = 5x + 2
3x = y + 10
3x = y + 10
3x = 5x + 2 + 10
3x = 5x + 12
3x - 5x = 12
-2x = 12
x = -6
substitute x = -6 into y = 5x + 2
y = 5(-6) + 2
y = -30 + 2
y = -28
x = -6, y = -28
hope this helped, God bless!
Answer:
32.66 units
Step-by-step explanation:
We are given that
Point A=(-2,-4) and point B=(1,20)
Differentiate w.r. t x
We know that length of curve
We have a=-2 and b=1
Using the formula
Length of curve=
Using substitution method
Substitute t=12x+14
Differentiate w.r t. x
Length of curve=
We know that
By using the formula
Length of curve=
Length of curve=
Length of curve=
Length of curve=
Length of curve=
Answer:
The mean amount spent = £14.80
The modal product is hoodies.
Step-by-step explanation:
Here
25 T shirts each costing £10 were purchased
Amount spent on T shirts = 25 × 10 = £250
30 key ring of £5 were purchased
Amount spent on key ring = 30 × 5 = £150
40 Hoodies for £25 each
Amount spent on Hoodies = 40 × 25 =£1000
30 CD's for £15 each
Amount spent on CD's = 30 ×15 = £450
Total amount spent = 250 +150 + 1000 + 450 = £1850
Total items purchased = 25 + 30 + 40 + 30 = 125
Mean amount spent =
The modal product is Hoodies as the maximum number of hoodies were purchased.